2022
DOI: 10.1016/j.jpeds.2021.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Bronchopulmonary Dysplasia and Neurodevelopmental Outcome at 2 and 5 Years Corrected Age

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…These findings support the potential use of NNNS exam findings prescriptively in infants with BPD for preventive and targeted interventions. Our findings are consistent with previous findings of cognitive and motor impairments at 24 months associated with BPD severity 30 31…”
Section: Discussionsupporting
confidence: 93%
“…These findings support the potential use of NNNS exam findings prescriptively in infants with BPD for preventive and targeted interventions. Our findings are consistent with previous findings of cognitive and motor impairments at 24 months associated with BPD severity 30 31…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, increasing evidence has suggested that BPD is not merely a lung disease but a systemic condition with short-term and long-term multiple organ implications[ 3 , 5 ]. Clinical and experimental findings demonstrated that chronic exposure to hyperoxia causes oxidative stress and leads to certain implications, including neurodevelopmental impairments[ 6 ], retinopathy of prematurity[ 7 , 8 ], renal vascular and tubular development impairments[ 9 , 10 ], and associated cardiac disease[ 11 , 12 ]. Notably, hyperoxia exposure in neonates results in long-term cardiac defects and renal abnormalities in later adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown a correlation between the severity of BPD and NDI, with severe BPD being associated with a higher incidence of NDI [21,22]. In this study, we have not assessed the association between severity of BPD and NDI, which was not possible due to a low number of infants with severe BPD in our cohort.…”
Section: Discussionmentioning
confidence: 93%